Afrikaners and the Boundaries of Faith in Post-Apartheid South Africa - Björnsdotter Teppo, Annika (Routledge Contemporary South Africa, 2022)
This book examines the shifting moral and spiritual lives of white Afrikaners in South Africa after apartheid. The end of South Africa's apartheid system of racial and spatial segregation sparked wide-reaching social change as social, cultural, spatial and racial boundaries were transgressed and transformed. This book investigates how Afrikaners have mediated the country's shifting boundaries within the realm of religion. For instance, one in every three Afrikaners used these new freedoms to leave the traditional Dutch Reformed Church (NGK), often for an entirely new religious affiliation within the Pentecostal or Charismatic churches, or New Religious Movements such as Wiccan neopaganism. Based on long-term ethnographic fieldwork in the Western Cape area, the book investigates what spiritual life after racial totalitarianism means for the members of the ethnic group that constructed and maintained that very totalitarianism. Ultimately, the book asks how these new Afrikaner religious practices contribute to social solidarity and integration in a persistently segregated society, and what they can tell us about racial relations in the country today. This book will be of interest to scholars of religious studies, social and cultural anthropology and African studies.